The top 100 articles on hepatitis C - Manar Aleid; Othman Tawfiq Almutairi; Latifah Alfahad; Mohammed Jameel; Nouf Almutairi; Bandar Al-Judiabi (Wolters Kluwer Medknow Publications, 2019)
Background: Hepatitis C infection is considered one of the most common hepatological infections. Many papers have been published, but none have listed the most influential work in the field of hepatitis C. Objectives: The aim of this study is to produce a bibliometric historical review on hepatitis C and its management. Methods: We underwent a title-specific search using Scopus database in 2017; using hepatitis C as our search term. The top 100 most cited articles were obtained and analyzed. Results: The top 100 articles received an average of 1273 citation per paper. The most productive years of publication ranged between 1999 and 2003 which accounted for 33 articles in our list. The top two journals in our list were New England Journal and Hepatology Journal with a contribution to 21 and 20 articles in our list, respectively. Research study category was accounted as the most common study category (60%). The top two specialties of contribution were Medicine (26 articles) and Hepatology (25 articles). Albrecht, J and Mchutchison have produced 9 and 8 articles, respectively, from our 160 authors list. The majority of the papers were created in the United States of America (62%). Conclusions: The identification and clustering of the top 100 most impactful work in hepatitis C serve as an excellent overview of the current trends of publication in the field of hepatitis C to identify areas of research inadequacy and to serves as an efficient guide to achieving evidence-based clinical practice.